Effect of Dangguibohyul-Tang, a Mixed Extract of Astragalus membranaceus and Angelica sinensis, on Allergic and Inflammatory Skin Reaction Compared with Single Extracts of Astragalus membranaceus or Angelica sinensis - Choi, You Yeon (Hindawi Publishing Corporation, 2016)

(untitled) (Evid Based Complement Alternat Med)
Dangguibohyul-tang (DBT), herbal formula composed of Astragalus membranaceus (AM) and Angelica sinensis (AS) at a ratio of 5 : 1, has been used for the treatment of various skin diseases in traditional medicine. We investigated the effect of DBT on allergic and inflammatory skin reaction in atopic dermatitis-like model compared to the single extract of AM or AS. DBT treatment showed the remission of clinical symptoms, including decreased skin thickness and scratching behavior, the total serum IgE level, and the number of mast cells compared to DNCB group as well as the single extract of AM- or AS-treated group. Levels of cytokines (IL-4, IL-6, IFN-γ, TNF-α, and IL-1β) and inflammatory mediators (NF-κB, phospho-IκBα, and phospho-MAPKs) were significantly decreased in AM, AS, and DBT groups. These results demonstrated that AM, AS, and DBT may have the therapeutic property on atopic dermatitis by inhibition of allergic and inflammatory mediators and DBT formula; a mixed extract of AM and AS based on the herb pairs theory especially might be more effective on antiallergic reaction as compared with the single extract of AM or AS.